2011
DOI: 10.3810/hp.2011.02.372
|View full text |Cite
|
Sign up to set email alerts
|

Use of Warfarin is Associated with Delay in Surgery for Hip Fracture in Older Patients

Abstract: Hip fracture patients who are using warfarin experience a longer waiting time for surgery, most likely due to more comorbidities. A more active approach to better management of comorbidities may reduce waiting time for surgery in warfarin users.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
30
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 16 publications
5
30
3
Order By: Relevance
“…This delay has been reported in previous studies [7, 8, 16, 24], although our study is the first, to our knowledge, showing the same association after regression analysis using these prognostic factors. Ryan et al [21] conducted a study with more than two million patients sustaining a fractured neck of the femur and reported that a time to the operating room in excess of 48 hours resulted in higher mortality, with an OR of 1.13 for the delayed group after controlling for multiple prognostic factors including comorbidity.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This delay has been reported in previous studies [7, 8, 16, 24], although our study is the first, to our knowledge, showing the same association after regression analysis using these prognostic factors. Ryan et al [21] conducted a study with more than two million patients sustaining a fractured neck of the femur and reported that a time to the operating room in excess of 48 hours resulted in higher mortality, with an OR of 1.13 for the delayed group after controlling for multiple prognostic factors including comorbidity.…”
Section: Discussionsupporting
confidence: 90%
“…The time taken to achieve a safe INR together with the presence of multiple comorbidities has the potential to delay surgical treatment, which conflicts with policy initiatives (such as the 2010 ‘Best Practice Tariff’ in the UK) that aim to improve patient outcomes by reducing delays in hip fracture surgery to less than 48 or 36 hours [5, 19]. Few studies have investigated the degree to which warfarin therapy is associated with delays to surgery [2, 7, 8, 16], and the degree to which such warfarin-associated care delays are associated with length of stay and mortality has not been reported, to our knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Surgery is often postponed to stabilize patients' clinical condition and optimize their hemodynamic status, since most patients admitted after a PFF are clinically unstable, dehydrated, anemic, and malnourished 36 . In addition, patients on antithrombotic medication prior to the fracture (highly common in the elderly for preventing thrombosis and atrial fibrillation) normally have their surgery delayed to prevent excessive intraoperative bleeding 37,38 . However, according to our findings a simple analysis of the use of antithrombotic medication does not appear to result in differences in time to surgery, since men on antithrombotic medication prior to surgery waited an average of 0.5 days longer than women.…”
Section: Discussionmentioning
confidence: 99%
“…There is firm evidence both for the requirement of protocols in hip fracture care, the morbidity associated with delays to theater in patients with hip fracture on warfarin, and the benefits of IVK administration. 11,12,14,15,[28][29][30][31] In particular, Leonidou et al found that IVK administration resulted in not only a decreased delay to theater but also the lowest rate of complications. 30 It is appropriate that any broad protocol-driven path of care should be met with a degree of concern, but for the early administration of IVK in the warfarinized population with hip fracture, the wealth of evidence supports its safe and beneficial use.…”
Section: Discussionmentioning
confidence: 99%
“…Admission to hospital with a hip fracture while on warfarin with a significantly (>2.0) raised international normalized ratio (INR) has been associated with delay to theater and a trend toward greater mortality. 11 Pharmaceutical intervention leads to improved outcomes 12,13 and while a range of reversal agents are available, including oral vitamin K, the administration of low-dose intravenous vitamin K (IVK) has been shown in particular to expedite time to theater.…”
Section: Introductionmentioning
confidence: 99%